Effects of Social Information on the Release and Expression of Gonadotropin-Inhibitory Hormone in Birds - Tobari, Yasuko; Tsutsui, Kazuyoshi (Frontiers in Endocrinology, 2019)
The social environment changes circulating hormone levels and associated behavior in animals. Although the perception of social information is processed in the brain, and peripheral hormonal levels are regulated mainly by the hypothalamus–pituitary–gonadal (HPG) axis, the specific neural circuitry and neurochemical systems that translate social signals into reproductive physiological responses were not well understood until the 2000s. Today, there is growing evidence that a neuropeptide localized in the hypothalamus, gonadotropin-inhibitory hormone (GnIH), is responsive to social information. GnIH was first identified in the quail hypothalamo-hypophyseal system and named for its ability to inhibit gonadotropin secretion. GnIH has thus begun to be regarded as a modulator, translating social stimuli into changes in the levels of peripheral reproductive hormones through the HPG axis. Here, we review previous studies that investigated the responses of the GnIH neuronal systems to social status, offspring, and the presence/absence of conspecifics, and describe the neurochemical pathways linking visual perception of a potential mate to rapid peripheral hormonal changes via the brain–pituitary endocrine system in birds.